2022
DOI: 10.1371/journal.pone.0258629
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cow’s milk with different PUFA n-6: n-3 ratios on performance, serum lipid profile, and blood parameters of grower gilts

Abstract: The concern with human health has increased the interest in producing foods enriched with polyunsaturated fatty acids (PUFA), directly or naturally, by inclusion in the animals’ diet. The positive effects such as antithrombotic, anti-inflammatory, and hypolipidemic have been observed in pigs and rats, used as human models for study. The present study evaluated the effect of cow’s milk with different lipid profiles on performance, serum fatty acid profile, biochemical analysis, and a complete blood count of gil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This result explains that PUFA in the TR diet is not available for milk fat synthesis, as well as the effects of PUFA uptake on the function of membranes and cell signaling, as well as the regulation of gene expression via various transcription factors. As a result, PUFA affects virtually every cell in the body [38]. Other studies reported that a higher ALA content in the milk of cows and sheep was due to a feed high in PUFA [12,36].…”
Section: Discussionmentioning
confidence: 99%
“…This result explains that PUFA in the TR diet is not available for milk fat synthesis, as well as the effects of PUFA uptake on the function of membranes and cell signaling, as well as the regulation of gene expression via various transcription factors. As a result, PUFA affects virtually every cell in the body [38]. Other studies reported that a higher ALA content in the milk of cows and sheep was due to a feed high in PUFA [12,36].…”
Section: Discussionmentioning
confidence: 99%